The “Fluad Case” in Italy: Could it have been dealt differently? - Miriam Levi; Ersilia Sinisgalli; Chiara Lorini; Francesca Santomauro; Martina Chellini; Paolo Bonanni (Human Vaccines & Immunotherapeutics, 2017)
During the influenza vaccination campaign 2014–2015, the reporting of 3 deaths within 48 hours of vaccination with Fluad brought the Italian Medicines Agency (AIFA) to pronounce the withdrawal of 2 batches of vaccine, based on the precautionary principle. Investigations by the Italian National Institute of Health, and by the Pharmacovigilance Risk Assessment Committee (PRAC), the committee at the European Medicines Agency (EMA) responsible for monitoring and assessing the safety profiles of human drugs, concluded that there was a lack of causality between the reported deaths and the vaccines administered. However, the media impact of the decision taken by AIFA, resulted in a lower influenza vaccination coverage compared with the previous years. The aim of our study was to identify possible critical points that may have led to a non-perfect management of the event. A review of the regulatory framework in place was performed, with a particular focus on the Guidelines on Good Pharmacovigilance Practices developed by the EMA to facilitate the signal management process. The management of reports involves the following steps: signal detection, its validation and confirmation, analysis and prioritization, assessment, recommendations for action and the exchange of information. In our opinion, both the signal detection phase and the phase of validation have been critical: the withdrawal of vaccine batches is possible even in case of a single suspected serious adverse reaction. However, aspects such as the biological plausibility, the presence of potential alternative causes and previous awareness should also be considered. Furthermore, the number of reported deaths was consistent with the expected background mortality rate in the vaccinated cohort. The disproportionate media coverage given to the AIFA decision resulted in a reduced vaccine confidence in the general population and in a decreased immunization coverage. Improving the communication on vaccine safety issues is crucial at this stage to restore a climate of trust in this powerful tool for primary prevention.